2019
DOI: 10.1097/gox.0000000000002296
|View full text |Cite
|
Sign up to set email alerts
|

Latissimus Dorsi Myocutaneous Flap in Immediate Reconstruction after Salvage Mastectomy Post-Lumpectomy and Radiation Therapy

Abstract: Background: Breast reconstruction after salvage mastectomy (SM) for recurrent cancer represents a challenge in preradiated patients due to the increased complication rate. Latissimus dorsi myocutaneous flap (LDMF) represents a good reconstructive option due to its versatility, safety, and adaptability. Methods: Fifty-nine patients treated in the Breast Surgery Unit at the University Hospital of Parma (Italy) between January 2010 and December 2017 for ip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
4
17
0
1
Order By: Relevance
“…19,21 Patients who underwent LD flap reconstruction had similar BREAST-Q scores when compared to other autologous reconstruction techniques. 6,22 This is consistent with a large survey study that reported similar BREAST-Q scores between the LD flap and other types of reconstruction. 18 The meta-analysis conducted in this review compared BREAST-Q scores in patients who underwent LD flap reconstruction with and without implants (Figure 2).…”
Section: Breast-qsupporting
confidence: 89%
See 2 more Smart Citations
“…19,21 Patients who underwent LD flap reconstruction had similar BREAST-Q scores when compared to other autologous reconstruction techniques. 6,22 This is consistent with a large survey study that reported similar BREAST-Q scores between the LD flap and other types of reconstruction. 18 The meta-analysis conducted in this review compared BREAST-Q scores in patients who underwent LD flap reconstruction with and without implants (Figure 2).…”
Section: Breast-qsupporting
confidence: 89%
“…A total of five studies met eligibility criteria and were included for data extraction and analysis (Figure 1). 6,16,19,21,22 Four studies consisted of level III evidence and one consisted of level IV evidence per the Levels of Evidence rating scale as described by the American Society of Plastic Surgeons (Table 2). 6,16,19,21,22 One study was a case-control design, and the remaining were retrospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of an LD flap to IBR has also been proposed for patients with prior BCS and radiotherapy. 21,29–31 Disa et al reported a 30% complication rate in 57 patients who underwent LD/IBR following BCS, with 70% of patients achieving a very good/excellent aesthetic result. 21 Similarly, Cattelani et al reported a 10% complication rate, good postoperative upper limb function, and high patient-reported satisfaction using LD/IBR after prior BCS and radiotherapy 29 ; however, neither report compared the outcomes of patients with LD/IBR to IBR.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of an LD flap to IBR has also been proposed for patients with prior BCS and radiotherapy. 21,[29][30][31] 29 ; however, neither report compared the outcomes of patients with LD/IBR to IBR. In our study, we found a similar overall and major complication rate between LD/IBR and IBR.…”
Section: Ementioning
confidence: 99%